PENGUATAN EKOWISATA GUNA MENINGKATKAN KUALITAS HIDUP MASYARAKAT DESA SIANGAN, KABUPATEN GIAMYAR - Gusti Ayu Made Rai Suarniti (Yayasan Nusa Cendekia Global, 2026)
This activity aims to strengthen ecotourism in order to improve the quality of life of the people of Siangan Village, Giamyar Regency. This is done by implementing various programs including, the community empowerment program is carried out with various activities, including: empowering the Siangan Village community in source-based waste management, developing interest in learning at the elementary school level in Siangan Village, promoting and planning the Siangan Village ecotourism route, preparing a tourism village master plan and assisting posyandu activities, empowering SMEs and livestock breeders in Siangan Village. Apart from these main activities, additional activities are also carried out, such as; matur piuning activities, activities for cleaning the KKN-PMM post area of ​​Siangan Village, helping ngayah in the banjar teruna of Siangan Village in preparation for the Pitra Yadnya ceremony, making wall magazines (mading) for the Siangan Village office, activities for helping to install flags at the Siangan Village office, attending invitation to take a leisurely walk to commemorate Seka Teruna Teruni's birthday in Banjar Bandung, cleaning the Gulung Tikeh Waterfall area in Siangan Village. This research was conducted using qualitative methods, and data collection was carried out using interview and field observation methods. The community was very enthusiastic in participating in a series of activities organized by Warmadewa University KKN students.